Prevalence of Vancomycin Resistant Enterococcus in Wastewater Treatment Plants and Their Recipients for Reuse Using PCR and MALDI-ToF MS - Adegoke, Anthony A.; Madu, Chibuzor E.; Reddy, Poovendhree; Stenström, Thor A.; Okoh, Anthony I. (Frontiers in Environmental Science, 2022)
The World Health Organization in 2017 listed Vancomycin resistant enterococci (VRE) among those with high priority for research. This study determined the efficiency of two wastewater treatment plants (WWTPs) in removing both vancomycin-resistant enterococci (VRE) and vancomycin-sensitive enterococci (VSE) from wastewater and the effect of their effluents on the receiving water bodies being reused. VRE and total enterococci (TE) respectively were isolated using Slanetz and Bartley agar with and without vancomycin from wastewater and river samples. Isolate speciation was confirmed by PCR and Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF) mass spectrometry (MS). Molecular methods were used for confirmation of presumptive VRE and for detection of van genes. Resistance to antibiotics was determined by the disk diffusion method. The TE and VRE counts of the two WWTPs influents ranged from 6.1 to 7.2 log10 CFU/100 mL and 4.3 to 6.7 log10 CFU/100 mL respectively while the effluent counts ranged from 0 to 4.4 log10 CFU/100 mL and 0 to 3.4 log10 CFU/100 mL for the chlorinated effluents. The TE and VRE counts of the recipient river samples were higher than the effluents. Exactly 186 (80.1%) isolates tallied with PCR as Enterococcus while 22 (9.5%) were positive by PCR but negative with MALDI-TOF. Enterococcus faecium and E. faecalis were the most abundant species. The isolates showed 34-100% resistance to quinopristin-dalfopristin, streptomycin, doxycycline, tetracycline, ciprofloxacin and cefixime. VanA (73.8%) were dominant among the isolates. The two WWTPs were efficient in reducing the VRE counts. Thus, the VRE in the river is most likely due to contamination from other sources and it may result in threat to human health when reused.